2009
DOI: 10.1038/aps.2009.88
|View full text |Cite
|
Sign up to set email alerts
|

Central cholinergic regulation of respiration: nicotinic receptors

Abstract: Nicotinic acetylcholine receptors (nAChRs) are expressed in brainstem and spinal cord regions involved in the control of breathing. These receptors mediate central cholinergic regulation of respiration and effects of the exogenous ligand nicotine on respiratory pattern. Activation of α4* nAChRs in the preBötzinger Complex (preBötC), an essential site for normal respiratory rhythm generation in mammals, modulates excitatory glutamatergic neurotransmission and depolarizes preBötC inspiratory neurons, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 107 publications
2
40
0
Order By: Relevance
“…[9] Since the implementation of the BTS campaign, prenatal and postnatal exposure to cigarette smoke has become one of the leading risk factors for SIDS. [15][16][17][18][19] In our study, maternal tobacco use increased the risk of SIDS by more than two-fold, which is similar to the finding from a meta-analysis by Zhang et al [16] that found a significantly increased risk of SIDS associated with prenatal maternal smoking (OR=2.25, 95% CI=2.03-2.50) and postnatal maternal smoking (OR=1.97, 95% CI=1.77-2.19). Exposure to nicotine, leading to decreased uteroplacental blood flow and chronic intrauterine hypoxia is one of the mechanisms linking maternal cigarette smoking to SIDS.…”
Section: Original Articlesupporting
confidence: 90%
See 1 more Smart Citation
“…[9] Since the implementation of the BTS campaign, prenatal and postnatal exposure to cigarette smoke has become one of the leading risk factors for SIDS. [15][16][17][18][19] In our study, maternal tobacco use increased the risk of SIDS by more than two-fold, which is similar to the finding from a meta-analysis by Zhang et al [16] that found a significantly increased risk of SIDS associated with prenatal maternal smoking (OR=2.25, 95% CI=2.03-2.50) and postnatal maternal smoking (OR=1.97, 95% CI=1.77-2.19). Exposure to nicotine, leading to decreased uteroplacental blood flow and chronic intrauterine hypoxia is one of the mechanisms linking maternal cigarette smoking to SIDS.…”
Section: Original Articlesupporting
confidence: 90%
“…Exposure to nicotine, leading to decreased uteroplacental blood flow and chronic intrauterine hypoxia is one of the mechanisms linking maternal cigarette smoking to SIDS. [16,18,19] Another mechanism linking SIDS to cigarette smoke has looked at the interaction between nicotine and nicotinic acetylcholine receptors in the brainstem and its effect on the central nervous system. In-utero exposure to nicotine can lead to changes in the brainstem sites responsible for cardiorespiratory control and arousal from sleep.…”
Section: Original Articlementioning
confidence: 99%
“…These elevated levels of nicotine are maintained through ingestion of the maternal milk at least until age P5 (Powell et al ., 2015). As a potent nicotinic acetylcholine receptor (nAChR) agonist, nicotine depolarizes hypoglossal motoneurons and can evoke high levels of action potential activity (Chamberlin et al ., 2002; Lamanauskas & Nistri, 2006; Shao & Feldman, 2009; Pilarski et al ., 2012). In addition, DNE leads to persistent desensitization of nAChRs (Gentry & Lukas, 2002; Pilarski et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most consistent central effect of ACh on respiratory activity has been reported to be excitatory (Bianchi et al, 1995;Shao and Feldman, 2009). Recently, experiments performed on in vitro medullary slices from neonatal rodents (Shao and Feldman, 2000 showed that increases in respiratory frequency are produced by the activation of both nicotinic ACh receptors (nAChRs) and muscarinic ACh receptors (mAChRs) in the pre-Bötzinger complex (preBötC), a medullary region that has been proposed to play a crucial role in respiratory rhythm generation in mammals (Smith et al, 1991;Feldman and Del Negro, 2006).…”
Section: Introductionmentioning
confidence: 92%